Sampling time is crucial for measurement of aerobic exercise-induced oxidative stress - Yiannis, M.; Jamurtas, A. Z.; Nikolaidis, M. G.; Fatouros, I. G.; Koutedakis, Y.; Papassotiriou, I.; Kouretas, D. (Medicine & Science in Sports & Exercise, 2007)
Purpose: To thoroughly investigate the time-course changes of several commonly used markers of oxidative stress by performing serial measurements during a 24-h period after an acute bout of strenuous cardiovascular exercise.